2022
DOI: 10.1021/acs.est.2c01535
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Sequestration in the Form of Recalcitrant Dissolved Organic Carbon in a Seaweed (Kelp) Farming Environment

Abstract: Under climate change scenarios, the contribution of macroalgae to carbon sequestration has attracted wide attention. As primary producers, macroalgae can release substantial amounts of dissolved organic carbon (DOC) in seawater. However, little is known about the molecular composition and chemical properties of DOC derived from macroalgae and which of them are recalcitrant DOC (RDOC) that can be sequestered for a long time in the ocean. In the most intensive seaweed (kelp) farming area (Sanggou Bay) in China, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 73 publications
(167 reference statements)
0
25
0
Order By: Relevance
“…However, most related investigations have only considered the direct absorption of these substances by the seaweed itself ( 44 46 ). Admittedly, direct absorption by seaweed is the dominant element fixation pathway; however, the microbes related to seaweed cultivation in biogeochemical cycles also contribute substantially ( 47 ). Our study results revealed that seaweed culture activities effectively promoted the biogeochemical cycles of bacterioplankton in the culture areas.…”
Section: Resultsmentioning
confidence: 99%
“…However, most related investigations have only considered the direct absorption of these substances by the seaweed itself ( 44 46 ). Admittedly, direct absorption by seaweed is the dominant element fixation pathway; however, the microbes related to seaweed cultivation in biogeochemical cycles also contribute substantially ( 47 ). Our study results revealed that seaweed culture activities effectively promoted the biogeochemical cycles of bacterioplankton in the culture areas.…”
Section: Resultsmentioning
confidence: 99%
“…Macroalgae can release a large amount of DOC to the environment during growth, and this makes macroalgae have a high carbon sink potential (Krause-Jensen and Duarte, 2016; Ortega et al, 2019;Watanabe et al, 2020;Li et al, 2022). However, a variety of environmental stressors have significant effects on DOC release from macroalgae (Paine et al, 2021;Hurd et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…prolifera than in those without this macroalgae (Figure S6). As macroalgae are rich in sulfur-containing substances (e.g., sulfated polysaccharides), the much higher proportion of CHOS in the newly introduced DOC molecules suggests that these were derived mainly from U. prolifera as this was the dominant macroalgal species in our sampling area.…”
Section: Discussionmentioning
confidence: 99%